Alternative Measure of Dispersion in the Polar-Radar Chart Methodology for Activity Management - Pérez-Benedito, Miguel Angel (Archives of Business Research, 2025)
Dynamic Activity measured through Averaging periods allows obtaining geometric figures to explain the effects of decision-making on management Activities. The sides of the triangle are perimeter distances whose lengths are tensions of types of management adopted by the companies. The type of management are variations of a kind of management identify by hierarchical ordering of perimeter distances. Measurement of Activities is developed through sufficiency indicators based on angular relationships of each area. Furthermore, intersections of linear equations generated from polar coordinates of triangle vertices, whose tangents are the mean angles of the vertices, form an alternative center of the triangle, which represents an equitable distribution of effects the decision making on financial statements. The manuscript considers its distance to the Cartesian center as a measure of dispersion, improving the estimation models.